PENERJEMAHAN KALIMAT IMPERATIF DAN KESALAHANNYA DALAM KITAB AR RAḤĪQ AL MAKHTŪM KARYA SYAIKH SHAFIYYURRAHMAN AL MUBARAKFURI - Anis, Muhammad Yunus; Ash-Shidiqiyyah, Firstiyana Romadlon (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
This research analyzes the translation of imperative sentences in Ar Raḥīq Al Makhtūm book (2007) by Shaikh Shafiyyurahman Al Mubarakfuri which was created to participate in a scientific competition on sirah nabawiyah in Pakistan. The book was translated into Indonesian by Kathur Suhardi as Sirah Nabawiyah (2014), a translator graduating from a boarding school who has published several translated books from any sciences. This research aims to describe the translation and its errors that applied by translator on translating imperative sentences in Ar Raḥīq Al Makhtūm book. The translation of imperative sentences is divided into two parts, the translation of positive imperative sentences (84%) and the translation of negative imperative sentences (16%), while that translation errors of imperative sentence are divided into four parts among them, linguistic category errors (28%), surface strategy errors (16%), comparative analysis errors (8%) and communicative effect errors (48%). The research methodology was qualitative descriptive research, an analysis that carried out from collecting data by the observation method of reading, understanding and signing of imperative sentences so be able to distinguish between imperative sentences with others. After collecting the data, then classifies the data according to categories and presents all data regarding the translation and its errors of imperative sentences and finally making the conclusions based on data that has been found. It was found there were 103 imperative sentence translation data with 87 positive imperative sentence translation data and 16 negative imperative sentence translation data, while for translation errors of imperative sentence researcher founds 50 data with 14 data in linguistic category errors, 8 data in the surface strategy errors, 4 data in comparative analysis errors and 24 data in communivative effect errors.